The Influence of Physical Work Environment and Work Motivation on the Performance of Soldiers in the Yonarmed 19/105 Tarik with Job Satisfaction as an Intervening Variable - Awaludin Baihaqi; Veronika Santi Paramita (Fakultas Ekonomi dan Bisnis, Universitas Jenderal Achmad Yani, 2025)
The performance of the Yonarmed unit is assessed based on individual recapitulations conducted four times a year. The average performance score for 2021–2022 experienced a decline in each quarter, raising concerns that it may not meet the organization's targets. The purpose of this study is to analyze the influence of the physical work environment and work motivation on the performance of soldiers in the Yonarmed 19/105 Tarik, with job satisfaction as an intervening variable. The research method used is descriptive causality research. The data collection technique employed is a questionnaire, and data analysis is conducted using multiple regression analysis and path analysis with the assistance of SPSS 26.0. The study involved 83 soldier respondents. The physical work environment, work motivation, and job satisfaction simultaneously influence the performance of soldiers in the 19/105 Tarik Medan Artillery Battalion. The physical work environment has a positive effect on job satisfaction. Work motivation has a positive effect on job satisfaction. The physical work environment and work motivation influence job satisfaction. The physical work environment has a positive effect on performance. Work motivation has a positive effect on performance. Job satisfaction has a positive effect on performance. Job satisfaction mediates the influence of the physical work environment on performance. Job satisfaction mediates the influence of work motivation on performance.